Ultrawide implants for immediate molar extraction socket versus standard diameter fixtures in healed alveolar ridges of missing molars, one-year postloading evaluation: A randomized controlled trial - Farhan Durrani; Ekta Kumari; Anju Gautam; Sakshi Agarwal; Rashika Mularisekar; Shraddha Shilpi (Journal of Indian Society of Periodontology)
Background: This randomized split-mouth study aimed to evaluate the feasibility of ultrawide immediate implants in fresh extraction sockets of nonrestorable molars. The comparison was made with standard-diameter implants placed in healed ridges of missing molars. After 1 year of functional loading, both groups were assessed for crestal bone changes, implant stability, and soft-tissue remodeling. The null hypothesis proposed that immediate molar socket replacement with ultrawide implants would demonstrate superior outcomes compared to standard-diameter implants. Materials and Methods: Thirteen patients were recruited for this split-mouth study, each presenting with a hopeless molar in one quadrant and a partially edentulous ridge with a missing molar in the contralateral quadrant. The compromised molars were atraumatically extracted without flap reflection, followed by immediate placement of ultrawide diameter implants. In the opposing quadrant, missing molar sites were rehabilitated with standard-diameter implants. Crestal bone remodeling, implant stability, and soft-tissue maturation were evaluated 1-year postloading. Radiographic assessments and Osstell device measurements were performed at implant placement, 3 months postrestoration, and 1 year after prosthetic function. Results: The findings suggest that immediate flapless molar extraction helps preserve vascular integrity, and ultrawide diameter implants may serve as a viable treatment modality for molar replacement. The wider implant surface effectively dissipated occlusal forces, and bone dimensions were well maintained in terms of both width and length. Soft-tissue maturation, including attached gingiva thickness, was favorable after 1 year of prosthetic function. Healed partially edentulous ridges restored with standard-diameter implants also demonstrated stable functional outcomes at the 1-year follow-up. However, a notable limitation of this approach was the inadequate bone volume to accommodate the width of the missing molar crown, leading to occlusal and maintenance challenges. In addition, incomplete papillary fill around implant-supported restorations was observed due to reduced bony dimensions. Conclusion: The comparison between the two groups did not yield statistically significant differences, likely due to the limited sample size. Split-mouth studies involving patients with both hopeless and missing molars within the same arch are relatively uncommon. Nevertheless, immediate molar replacement using ultrawide diameter implants may offer a promising alternative to the delayed placement of standard-diameter implants for molar rehabilitation.